Transcriptomic analyses of Pinctada fucata martensii responses under stress of titanium dioxide nanoparticles - Li, Fengfeng; Liu, Jiaen; Gao, Zixin; Yang, Chuangye; Sun, Liwei; Liao, Yongshan; Deng, Yuewen (Frontiers in Marine Science, 2024)
Titanium dioxide nanoparticles (TiO2-NPs) released into the environment is becoming more prevalent due to their increased usage, marine TiO2-NPs contamination is escalating concerns in coastal areas. To understand the potential impact of TiO2-NPs on transcript changes in pearl oyster (Pinctada fucata martensii), transcriptome analysis on the gill tissues of pearl oysters was conducted after 14-day TiO2-NPs exposure and 7-day brief recovery. A total of 911 differentially expressed genes (DEGs) were identified between the control group (TC) and the experimental group (TE) exposed to 14-day TiO2-NPs. Gene ontology (GO) analyses of the DEGs demonstrated their substantial enrichments in functions related to “hydrolase activity”, “oxidoreductase activity”, and “DNA integration”. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analyses of the DEGs indicated enrichment in several pathways, including “ubiquitin-mediated protein hydrolysis”, “ECM-receptor interactions”, “NOD-like receptor signaling pathway”, “Toll-like receptor”, and “FOXO signaling pathway”. This suggests that exposure to TiO2-NPs intensifies oxidative stress and apoptosis in pearls oysters, leading to negative effects such as disrupted protein homeostasis, decreased biomineralization activity, reduced neuronal excitability, weakened immune response, and reduced cellular metabolism. Transcriptome analysis identified 844 DEGs between the TE and recovery group (TR), which underwent a 7-day brief recovery period. GO analyses of the DEGs demonstrated their substantial enrichments in functions related to “DNA integration”, “obsolete oxidation-reduction process”, and “proteolysis”. KEGG pathways analyses of the DEGs indicated enrichment in several pathways, including “lysine degradation”, “glycine, serine, and threonine metabolism”, and “NOD-like receptor signaling pathway”. The findings indicated that although pearl oysters showed only slight relief after 7 days of brief recovery, they continued to experience negative effects from TiO2-NP exposure. Our findings shed light on the complex responses of pearl oysters to TiO2-NPs stress and offer valuable theoretical insights into the toxicological impact of TiO2-NPs on pearl oysters.